In Vitro Study of Biological Activity of Tanacetum vulgare Extracts - Olga Babich; Viktoria Larina; Olesia Krol; Elena Ulrikh; Stanislav Sukhikh; Maxim A. Gureev; Alexander Prosekov; Svetlana Ivanova (MDPI AG, 2023)
Tanacetum vulgare is an herbaceous plant widely used in folk medicine. It is rich in phenolic acids and flavonoids, which have pharmacological and medicinal properties, such as anthelmintic, antispasmodic, tonic, antidiabetic, diuretic, and antihypertensive. This study aimed to confirm the presence of biologically active substances in Tanacetum vulgare and to determine the pharmacological spectrum of biological activity of Tanacetum vulgare extract components. When preparing Tanacetum vulgare extracts, the highest yield was observed when using the maceration method with a mixture of solvents methanol + trifluoroacetic acid (22.65 ± 0.68%). The biologically active substances in Tanacetum vulgare extract samples were determined using high-performance liquid chromatography. Biologically active substances such as luteolin-7-glucoside (550.80 mg/kg), chlorogenic acid (5945.40 mg/kg), and rosmarinic acid (661.31 mg/kg) were identified. Their structures were determined. The experiments have confirmed the antioxidant and antibacterial activities. Secondary metabolites of Tanacetum vulgare extracts have been found to have previously unknown biological activity types; experimental confirmation of their existence will advance phytochemical research and lead to the development of new drugs.